2001
DOI: 10.1063/1.1405427
|View full text |Cite
|
Sign up to set email alerts
|

Eu 3+ -doped microcavities fabricated by sol–gel process

Abstract: The fabrication of microcavities by a sol–gel process and their optical properties are described. The cavities are constituted of an Eu3+-doped SiO2 active layer inserted between two Bragg mirrors, fabricated by stacking alternatiely undoped TiO2 and SiO2 sol–gel thin films. Eu3+ luminescence modification due to the cavity effect, intensity enhancement and modification of the line shape has been observed, and shows a cavity quality factor of 1200. The reflectivity factor of the associated Bragg mirrors reaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 14 publications
2
41
0
5
Order By: Relevance
“…Previous studies have shown that sol-gel waveguides can be easily fabricated owing to their high refractive index and that they typically exhibit optical propagation losses of less than 1 dB cm -1 . [15] Such sol-gel matrices have also been found to be excellent hosts for organic chromophores, [16,17] erbium cations, [18,19] and indeed quantum dots (QDs). [20][21][22] Truly optically 'photoluminescence (PL)-active' waveguides have been however ridden with obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that sol-gel waveguides can be easily fabricated owing to their high refractive index and that they typically exhibit optical propagation losses of less than 1 dB cm -1 . [15] Such sol-gel matrices have also been found to be excellent hosts for organic chromophores, [16,17] erbium cations, [18,19] and indeed quantum dots (QDs). [20][21][22] Truly optically 'photoluminescence (PL)-active' waveguides have been however ridden with obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…This corresponds to a waveguide loss of 0.009 dB/ cm, which is the lowest loss reported to date for sol-gel silica-on-silicon technology. 14,15 These high quality factors allow the observation of Raman emission with threshold pump powers below a milliwatt. In this case, a single-frequency tunable externalcavity laser operating around 1550 nm band was used to pump the microcavity.…”
mentioning
confidence: 99%
“…The thickness e is the parameter which is going to change in the simulations. allow the manufacturing of this structure to test experimentally our results [14].…”
Section: Complex Dispersion Relationmentioning
confidence: 99%